Delivering business intelligence with Microsoft SQL server 2005 - Larson, Brian (Essential skills for database professionals., 2006)
Data warehouse administrators, Business Intelligence (BI) solution developers, and BI analysts will find out how to get the most out of Microsoft's powerful BI tools which are included free in SQL Server 2005. This practical, start-to-finish guide explains how to develop a comprehensive, secure, integrated, and highly available BI solution. Readers will learn to set up the database, mine and analyze data, and deliver the results. It provides a complete understanding of the BI lifecycle and the Microsoft tools designed to handle each step in that lifecycle. It features real-world example scenarios so readers can apply their knowledge. All code will be available free for download.